(3GdbGfhf GdJLGQj (B:s (3GdYbhO GdJLGQjI HYedjGJ GdHfhc habG dCMcGe bGfhf GdJLGQI Qbe (B17(3dSfI (B1999 /s - (3GdHGQhOj, Ydjs; (3eMeO aQjO GdYQjfjs ((3GdGScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 2000)
(3YbO GdHjY GdJLGQj, YbO GdhcGdI HGdYehdI, YbO GdSeSQI, GdQgf GdJLGQj, YbO Gdfbd, aj YedjGJ GdHfhc GdJLGQjI, YedjGJ GdGjOGY, YedjGJ GdGFJeGfs
Keywords: (3GdHfhcs; (3GdYbhO GdJLGQjIs; (3GdbGfhf GdJLGQjs